Actualización de software en el laboratorio informático y su resultado en las clases virtuales con los estudiantes de la Escuela de Educación Básica Antonio Parra Velasco cantón Mocache, Provincia de Los Ríos, año 2022 - López Intriago, Jorge Luis (2022)
This thesis project consists of updating software in the computer laboratory and its result in virtual classes with the students of the "Antonio Parra Velasco" school of basic education, Mocache canton, Los Ríos province, year 2021. Observing the problems there is no maintenance plan assumed in the institution, so that the computer laboratory and its effect on the process contribute to the teaching and learning of students, with a maintenance plan will contribute to the proper use of the laboratory of computation With the objectives, to determine the software update in the computer laboratory and its result in the virtual classes with the students of the "Antonio Parra Velasco" basic education school and to analyze its effect on the teaching-learning process of the students. In the present investigation, it will be carried out under the qualitative-quantitative paradigm, since the social problem will be taken into account, thus studying its context and proposing a direct and participatory observation with the problem. It also raises what are the possible causes that arise in the problem, in addition, the alternative and its validity are sought. This project describes a preventive and corrective maintenance plan for the computers in the laboratory of the "Antonio Parra Velasco" school of basic education and the way in which an adequate administration can be developed based on the need to keep it always functional so that the students can develop their practices without any alteration. Performing maintenance on the laboratory's technological equipment is for the purpose of determining their operating conditions and attempting to reduce potential failures that may occur. The critical factors are the possible damages, whether due to lack of cleanliness or carelessness of the administrators, although misuse by students that could alter normal functioning must not be ignored. It is for this reason that the development of a manual is proposed to try to cover possible technological shortcomings. As a result, in this research, there is a better performance of the computers within the laboratory with a better management and internet speed that facilitates the teaching and learning of the Antonio Parra Velazco Basic Education school.